Presence of fetal DNA in maternal exhaled breath condensate - TIPLAMAZ, SITKI; ÜNAL ADINIR, CANAN; AKKİPRİK, MUSTAFA (My University, 2022)
© 2022 John Wiley & Sons Ltd.Objectives: Cell-free DNA has been found in all body fluids, but DNAs emerging from locations that are not in direct contact with breath in exhaled breath condensate (EBC) are yet to be found. The potential of EBC for prenatal and cancer screening prompted us to investigate whether fetal DNA is present in maternal EBC. Method: A total of 20 pregnant women\"s EBC and blood samples were collected. Four Y chromosome-specific assays were tested on all EBC and plasma samples by quantitative PCR (qPCR). The best-performing assay was used for digital droplet PCR (ddPCR) on all EBC and the six plasma samples. Results: The sex of the fetuses was accurately determined from plasma samples. DNA sequences could not be properly amplified in EBC samples by the qPCR. By ddPCR, the Y chromosome sequence was amplified in two of the 11 EBC samples, from women carrying male fetuses (2/11), and the Y chromosome sequence was not amplified in the EBC of women carrying female fetuses (9/9). Exhaled breath condensate ddPCR result\"s specificity was 100%, the detection rate of Y chromosome was 18.18% (2/11), and the corrected accuracy was 59.09%. Conclusion: Our finding of \"the presence of fetal DNA in maternal EBC\", despite the low detection rate, might have a major impact on prenatal diagnosis and cancer screening.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Cerrahi Tıp Bilimleri; Kadın Hastalıkları ve Doğum; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Surgery Medicine Sciences; Obstetrics and Gynecology; Life Sciences; Molecular Biology and Genetics; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; KADIN HASTALIKLARI & DOĞUM; GENETİK VE KALITIM; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; OBSTETRICS & GYNECOLOGY; GENETICS & HEREDITY; Doğum ve Jinekoloji; Genetik (klinik); Genetics (clinical)